Four different gene-related cone–rod dystrophy: clinical and genetic findings in six Chinese families with diverse modes of inheritance - Li, Zhen; Cheng, Wanyu; Zi, Feiyin; Wang, Juan; Huang, Xiaoyu; Sheng, Xunlun; Rong, Weining (Frontiers in Genetics, 2023)
Purpose: To investigate pathogenic variants in six cone-rod dystrophy (CORD) families with various inheritance patterns by using whole-exome sequencing and analyzing the phenotypic features. Method: Six CORD families have been enrolled in Ningxia Eye Hospital for this study. The probands and their family members received comprehensive ophthalmic examinations, and DNA was abstracted from patients and family members. Whole exome sequencing was performed on probands to screen the causative variants and all suspected pathogenic variants were determined by Sanger sequencing and co-segregation analysis was performed on available family members. The pathogenicity of novel variants was predicted using silico analysis and evaluated according to ACMG guidelines. Results: In the six families, two families were assigned as X-linked recessive, two families were assigned as autosomal recessive, and two families were assigned as autosomal dominant. Pathogenic variants were detected in CACNA1F in 2 X-linked recessive probands, among which family 1 had hemizygous frameshift variant c.2201del (p.Val734Glyfs*17) and family 2 had hemizygous missense variant c.245G>A (p.Arg82Gln). Both probands had high myopia, with fundus tessellation accompanied by abnormalities in the outer structure of the macular area. The homozygous splice variant c.2373+5G>T of PROM1 and the homozygous nonsense variant c.604C>T (p.Arg202Ter) of ADAM9 were detected in two autosomal recessive families of the probands, respectively. Both probands showed different degrees of atrophy in the macular area, and the lesions showed hypofluorescence changes in autofluorescence. The heterozygous variation of CRX c.682C>T (p.Gln228Ter) was detected in two autosomal dominant families. The onset age of the two probands was late, with better vision and severe macular atrophy. According to ACMG guidelines and the analysis of online silico tools, all variations were labeled as potentially harmful or pathogenic. Conclusion: Pathogenic variants in CACNA1F, PROM1, ADAM9, and CRX genes were identified in six families affected by diverse inheritance patterns of CORD. Furthermore, the potential impact of the nonsense-mediated decay (NMD) mechanism on the manifestation of CORD phenotypes was examined and addressed. Simultaneously, the spectrum of pathogenic variants and clinical phenotypes associated with the CORD gene was expanded.